Improving Process Writing with the Use Authentic Assessment - Muhammad Noor bin Abdul Aziz; Nurahimah Mohd Yusoff (International Journal of Evaluation and Research in Education (IJERE), 2016)
The paper discusses on how process writing is improved with the use of authentic assessment in an English Language classroom. Eleven primary school children from Year 4 in a rural school in Sabah are the participants of the study. Data were collected by observing them during the English Language lessons and at the end of the series of observations, an interview session was conducted. The results of the study revealed thatusing authentic assessment to assess young learners’ writing skills is beneficial and effective in helping them to write better in the English Language classroom. The presentation will therefore provide suggestions for the use of more authentic assessment in the classroom, particularly in English Language teaching and learning.